(untitled) (Swiss Medical Weekly, 2018)
OBJECTIVE To assess the clinical implementation and report preliminary results of a novel technique called the Ozaki procedure for stentless aortic valve replacement through reconstruction of the valve leaflets from autologous pericardium. METHOD Between September 2015 and May 2017 30 patients (20 males, mean ± standard deviation age 66.83 ± 10.55 years) suffering from aortic stenosis (AS, n = 7), aortic regurgitation (AR, n = 12), or a combination of both (AS/AR, n = 11) were assigned for an Ozaki procedure. The glutaraldehyde-treated autologous pericardium was intraoperatively customised and tailored according to individual sinus measurements and appropriate Ozaki templates (CE marked). RESULTS Mean and peak preoperative transvalvular pressure gradients in patients with AS were 46.34 ± 14.71 and 78.00 ± 22.54 mm Hg, respectively and effective orifice area was 0.93 ± 0.26 cm2. Ejection fraction was preserved at 57.37 ± 10.33%. Twenty-four valves were tricuspid and 6 bicuspid; 13 patients had concomitant cardiac surgery (coronary artery bypass graft, mitral valve repair, replacement of ascending aorta). ​ Mean ± SD cross-clamp time for replacement only was 85.18 ± 18.10 minutes and perfusion time 104.76 ± 38.52 minutes. Cusp sizes were 27.76 ± 3.52 mm for the left coronary cusp (CC), 28.20 ± 3.51 mm for the right CC and 29.20 ± 3.34 mm for non-CC. Mean and peak postoperative gradients decreased to 8 ± 3.55 and 14.8 ± 6.21 mm Hg, respectively. Mean length of stay on the intensive care unit was 2.19 ± 2.34 days and in-hospital stay was 8.81 ± 2.04 days after isolated Ozaki procedures. No pacemaker had to be implanted after an isolated Ozaki procedure. Thirty-day mortality was 3.33% (n = 1). After 3 months, no patient presented with aortic stenosis, and regurgitation of the substituted valves was graded nil/trace in 85.71%, mild in 10.71%, and moderate in 3.57% of the patients. Ejection fraction remained unchanged at 58.89 ± 11.29%. No reoperation was required within the first 3 months. CONCLUSION This aortic valve replacement technique has become available only recently. In our experience, it can be mastered after a relatively short training period, and has become part of our routine clinical toolbox. The use of autologous pericardium in combination with excellent haemodynamics may have the potential to overcome the structural disadvantages of biological aortic valves, to be beneficial in infective endocarditis, and to represent an alternative for patients with small annuli.